The Structure of Discourse: A Corpus-Based Cross-Linguistic Study - Morten Gylling (Copenhagen Business School (CBS), 2013)
Effective communication requires texts to be organised into a coherent discourse structure. But languages vary considerably in how they do this, posing a challenge for effective intercultural communication. Instead of relying on our own preferred persuasion style to be the most effective, we need to take into consideration that people with different linguistic and cultural backgrounds do not necessarily employ the same linguistic means in similar communication situations. This is of particular importance in a business context, and a profound understanding of cross-linguistic differences in the organisation of argumentative texts is needed. In order to address this challenge, this thesis presents a study of structural characteristics in argumentative texts across three different languages. The aim of the study is to examine some of the linguistic means that writers of different languages employ when creating persuasive discourses. The study is based on 150 Danish, English and Italian speeches held by Members of the European Parliament in their native language. The linguistic means under investigation are conceptualised as belonging to three different structural domains which account for different ways of linking discourse units in a text: a syntactically organised text structure, a rhetorically organised discourse structure and an information packaging organised information structure. The structural domains are defined from a cognitive-functional perspective and juxtaposed into a single analytical framework. The analyses show that writers across the three languages generally use the same rhetorical relations to build up persuasive discourses. But the analyses also reveal that the Danish, English and Italian writers textualise relations differently. The Danish writers use almost exclusively finite verb forms in coordinate and subordinate structures. The English writers tend to avoid explicating the rhetorical relations between discourse units, and the Italian writers tend to include more units inside the same sentence than the Danish and English writers. The analyses also suggest that the cross-linguistic differences in textualisation can be correlated with certain persuasive strategies. The Danish writers tend to persuade by analogy, making use of typical features from narratives. The English writers make use of presentational persuasion style, involving themselves in a more personal way than the Danish and Italian writers. And lastly, the Italian writers make use of typical features from quasilogical persuasion style, adopting a formal register and argumentation. This thesis formulates an analytical framework for a systematic investigation of the structure of discourse across languages, pairing theories and methods from the two parallel disciplines of linguistics and rhetoric in order to gain more insights into effective intercultural communication.
hdl:10398/8794
Keywords: 650